The submandibular sialolithiasis in an eight-year-old child: a case report - Khatri, Rajkumari P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Sialolithiasis is a commonly encountered disease of the salivary glands and represents up to 30-50% of all salivary gland diseases. However, the condition is rarely encountered in the paediatric population. The formation of a salivary stone is believed to be secondary to the deposition of calcium salts around a nidus, which is commonly associated with desquamated epithelial tissue or sloughing from a recent bacterial infection. Patients with submandibular sialolithiasis usually present with acute swelling over the neck associated with pain, fever, and purulent intraoral discharge. The calculi were located on the right in 100.0% of paediatric patients. Moreover, 20.0% of paediatric patients exhibited sialoliths in the glands. In this paper, we present the case of an 8-year-old male child who presented with a history of swelling over the right submandibular region since four months and had not responded to the conservative treatment given for the last four months. On examination, a small, rounded salivary calculus was found at the Wharton duct orifice near the papilla. A minimally invasive surgical procedure of intraoral excision of the calculus was done, and the patient was prevented from undergoing surgical excision of the gland. A large number of relatively small and distal sialoliths in paediatric patients can be removed using intraoral retrieval under local or general anesthesia. The clinical evaluation of the entire salivary tract with a high index of suspicion helps in early diagnosis and avoids the development of an abscess and other complications that may require surgical excision of the gland.